Containing Eve’s daughters? The education, fashioning and socialisation of women within three elite households of the West Country c. 1525-1660. - Bowness, C (2016)
This thesis focuses on the education of women in three elite West Country households, the Arundells of Lanherne, the Edgcumbes of Cotehele and Mount Edgcumbe and the Reynells of Forde, in particular Dorothy Arundell (1560-1613), Anne Edgcumbe Dowriche (1560-96) and Lucie Reynell (1577-1652). It also notes the experiences of women in previous generations, which influenced education provision for girls. As early modern English women did not access the formal educational institutions of the universities or the Inns of Court, this thesis encourages a broader definition of education, to include teaching and vocational training in informal settings. It turns primarily to the household, where women spent most of their lives, but avoids a narrow focus on negative aspects of patriarchal society, which would place emphasis on the containment of women and what they could not do. Instead, it takes a positive approach, using case studies to explore the women’s experiences and achievements. These achievements act as pointers towards the depth and breadth of theoretical knowledge and level of practical skills each woman required to accomplish them. It demonstrates that rather than contained, Anne, Dorothy and Lucie were self-contained and confident. This thesis concludes that local and family archives contain more evidence, linked to the educational experiences of women, than many imagine. It encourages local historians to conduct further research, on individual women, in their own regions, to provide further evidence to refute claims that elite women received little or no education in early modern England.